Improving Health Behavior Standard Through Modern Islamic Boarding School (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
The purpose of this study is to explain health behavior standard of modern Islamic boarding school. The sample was determined purposively in Modern Islamic Boarding School in Banten Province, of Indonesia and respondents were 90 people with simple random techniques. This research uses descriptive quantitative method and data from the questionnaires. The results of this research showed that health behavior residents of Islamic boarding schools can be improved by predisposing factors such as (category of fairly good education and good income category), enabling factors (facilities for clinic/poskestren included: room/place, the medical and non-medical equipment and medicines in the good category) and strengthening factors (cadres of Poskestren, management aspect of clinic/poskestren, aspect of observation on the health and from the aspect of healthy behavior in the good category). A dominant factor to improving health behavior residents of Islamic boarding schools is the reinforcing factor.